Effect of electron irradiation on mechanical, tribological and thermal properties of polytetrafluoroethylene - Ormanbekov, K; Rakhadilov, B.K.; Zhassulan, A.Zh.; Mukhamedov, N.E.; Shynarbek, A.B.; Magazov, N.M. (Eurasian Journal of Physics and Functional Materials, 2026)
The article presents the study results of the electron irradiation effect on the mechanical, tribological and thermal properties of polytetrafluoroethylene (PTFE). The results allow a better understanding of the processes occurring in the structure of PTFE under irradiation and reveal potential applications of the modified material with improved tribological characteristics, high thermal resistance and mechanical strength. In this work the samples were tested for wear resistance and thermal stability. It was found that the effect of electron irradiation leads to a significant increase in the microhardness of the material by 1.5 times compared to the initial state. However, degradation of the thermal properties of the polymer due to the breakage of molecular chains is observed, which may affect its resistance to high temperatures and mechanical stresses. Such studies are important to advance the knowledge of the effects of irradiation on the structures and properties of polymeric materials. These results highlight the complex interaction between electron irradiation and the properties of polytetrafluoroethylene, which is important for understanding and optimising the application of this polymer in various engineering and industrial applications.Recommended CitationOrmanbekov, K. D.; Rakhadilov, B. K.; Zhassulan, A. Zh.; Mukhamedov, N. E.; Shynarbek, A. B.; and Magazov, N. M. (2023) "Effect of electron irradiation on mechanical, tribological and thermal properties of polytetrafluoroethylene," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 4, Article 2.DOI: https://doi.org/10.32523/ejpfm.2023070402